Learning Strategies Used To Develop English Speaking Skill: A Case Study Of To Higher Achievers At Stikes 'Aisyiyah Surakarta - Erfinah, Yulianti (2012)
This study belongs to learning strategies used by the higher achievers of stikes "aisyiyah Surakarta to develop speaking skill. It is aimed to describe the learning strategies used to develop English speaking skill: a case study of to higher achievers at stikes "aisyiyah Surakarta. Learning strategies to develop English speaking skill divided into four aspects. The aspects are fluency, pronunciation, vocabulary repertoire, and grammar knowledge. This research is conducted by analyzing the data by employing the concept of Miles, Huberman and Spradley. The type of this study is case study. The subject of this study is a student of higher achievers at stikes "aisyiyah Surakarta. The writer uses interview and observation to collect the data. The result of analysis shows that there are four aspects, that is: (1) The learning strategies used to develop fluency there are metacognitive strategy that is organizational planning, cognitive strategy that is rehearsal, and social/ affective strategy that is self-talk. (2) The learning strategies used to develop pronunciation there is cognitive strategy that included note taking and rehearsal. (3) The learning strategies used to develop vocabulary repertoire there is cognitive strategy that included translation and note taking. (4) The learning strategies used to develop grammatical knowledge there are metacognitive strategy that is organizational planning and cognitive strategy there are note taking and translation.